Rotaxane Co-II complexes as field-induced single-ion magnets - Cirulli,M; Salvadori,E; Zhang,Z-H; Dommett,M; Tuna,F; Bamberger,H; Lewis,JEM; Kaur,A; Tizzard,GJ; van,Slageren J; Crespo-Otero,R; Goldup,SM; et al. (Angewandte Chemie International Edition, 2021)
Mechanically chelating ligands have untapped potential for the engineering of metal ion properties. Here we demonstrate this principle in the context of CoII-based single-ion magnets. Using multi-frequency EPR, susceptibility and magnetization measurements we found that these complexes show some of the highest zero field splittings reported for five-coordinate CoII complexes to date. The predictable coordination behaviour of the interlocked ligands allowed the magnetic properties of their CoII complexes to be evaluated computationally a priori and our combined experimental and theoretical approach enabled us to rationalize the observed trends. The predictable magnetic behaviour of the rotaxane CoII complexes demonstrates that interlocked ligands offer a new strategy to design metal complexes with interesting functionality.